2016
DOI: 10.1007/s00170-016-8803-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of interface compatibility during ball spinning of composite tube of copper and aluminum

Abstract: As a new attempt, ball spinning was used to man-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Bimetal composite ring is widely used in the petrochemical industry, automobile, ship, and equipment manufacturing because its outer layer has high strength and hardness and the inner layer has wear resistance and corrosion resistance. The composite methods of bimetal rings mainly include mechanical bonding, 16 centrifugal casting bonding, 7,8 hot rolling bonding, 9,10 and welding 11,12…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bimetal composite ring is widely used in the petrochemical industry, automobile, ship, and equipment manufacturing because its outer layer has high strength and hardness and the inner layer has wear resistance and corrosion resistance. The composite methods of bimetal rings mainly include mechanical bonding, 16 centrifugal casting bonding, 7,8 hot rolling bonding, 9,10 and welding 11,12…”
Section: Introductionmentioning
confidence: 99%
“…Bimetal composite ring is widely used in the petrochemical industry, automobile, ship, and equipment manufacturing because its outer layer has high strength and hardness and the inner layer has wear resistance and corrosion resistance. The composite methods of bimetal rings mainly include mechanical bonding, [1][2][3][4][5][6] centrifugal casting bonding, 7,8 hot rolling bonding, 9,10 and welding 11,12 The advantage of mechanical bonding is that the process is simple, but the bonding strength of the interface formed by mechanical bonding is low, which easily leads to delamination of the bonding layer during the service process, leading to failure. The advantage of centrifugal casting bonding is that the strength of the interface bonding is high, but the process of centrifugal casting is complex, and the casting process is easy to appear mixed flow at the interface, leading to unstable quality.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the microstructure and interfacial strength of aluminum/aluminum, copper/aluminum, and stainless steel/aluminum bimetal tube spinning were studied to manufacture bimetal composite tube with interfacial bonding strength. To further improve the coordination of the two-layer tube, Jiang et al [12] used ball spinning for forming Cu/Al bimetal tube. In addition, it was found that the yield strength of the inner and outer tube materials affects the coordination of the spinning of the bimetal tube and affects the elongation of clad tube and base tube.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [4] analyzed the folding defects formed by ball spinning at the bottom of the inner grooves of copper tubes according to the results of finite-element analysis. Jiang et al [5,6] simulated the ball spinning of a nickeltitanium shape memory alloy tube by the rigid-viscoplastic finite-element method and investigated the interface compatibility of the composite tube of copper and aluminum during ball spinning. In [7], the finite-element method was used to simulate the thin-walled tube ball spinning, and the reasonable process parameters were obtained.…”
Section: Introductionmentioning
confidence: 99%